Digital Transformation And Financial Performance Of Hotel Companies In Indonesia: An Empirical Study Before And After The Covid-19 Pandemic - Adi Sopyan (Institute of Advanced Knowledge and Science, 2026)
This study examines the impact of digital transformation on the financial performance of hotel companies listed on the Indonesia Stock Exchange (IDX) for the period 2015–2023. Employing panel data regression with 25 sampled companies (225 firm-year observations), digital transformation is measured through a composite four-component index, while financial performance is captured by ROA, ROE, and Operating Expense Ratio (OER). Results reveal that digital transformation positively and significantly affects ROA (β=0.087; p<0.01) and ROE (β=0.134; p<0.01), and significantly reduces OER (β=-0.143; p<0.01). The COVID-19 pandemic moderates these relationships, weakening short-term profitability impacts while acting as a forced accelerator of digital adoption that strengthens long-term firm resilience.